The Effect of Fluid Flow Current to 30Âº Blades Achard Turbine Performance - Muhammad Faizal; Dodi Tafrant (Journal of Mechanical Science and Engineering, 2016)
Achard turbine is one kind of vertical axis water turbine that can use to low head water current. Achard turbine can use to river flow or irrigation canal. This is will make an additional function of river and irrigation canal to be a renewable energy resource. The experiment use three blades NACA 0020 Achard turbine in the irrigation canal at Belitang District, West Ogan Komering Ulu. The flow current is 0.55 m/s, 0.61 m/s, and 0.71 m/s. The result shows increasing of CP and CT by increasing of flow current. Maximum CP is 0.1797 at flow current 0.71 m/s. Maximum CT is 0.206 at flow current 0.71 m/s.